(untitled) (Research, Society and Development, 2025)
Staphylococcus caprae is a commensal microorganism in human and animal microbiota. Although infrequent, the literature reports this bacterium as being associated with invasive human infections. However, few studies describe the antimicrobial profiles of S. caprae strains, especially in developing countries. This paper aims to report the antimicrobial profiles of S. caprae samples isolated from blood cultures in tertiary hospitals in Brazil and investigate the antimicrobial profile worldwide. The sample identification was performed using the MALDI-TOF technique, and the antimicrobial susceptibility profile was evaluated according to the methodology standardized by BrCAST. The global antimicrobial profile was assessed through a brief review. It was observed that fifty percent of the Brazilian samples showed resistance to penicillin and ampicillin, and the fluoroquinolone profile ranged from resistant to susceptible with increased exposure. In the overall antimicrobial profile, β-lactam resistance was the most frequently observed. The results of this study are important and may assist in epidemiological monitoring and appropriate medical management.